Electrochemical jet manufacturing technology: From fundamentals to application. (September 2022) - Speidel, Alistair; Bisterov, Ivan; Saxena, Krishna Kumar; Zubayr, Mohamed; Reynaerts, Dominiek; Natsu, Wataru; Clare, Adam T.
Abstract: Electrochemical jet processing encompasses a group of non-contact and 'tool-less' technologies, relying on localised electrolyte jets to affect changes to the workpiece in a site-specific manner. This is achieved without thermally or mechanically modifying the underlying material giving rise to a unique class of manufacturing methods. Jet techniques have been applied to remove and deposit material selectively, for example to machine microscale pits and grooves, to process larger surface areas, and to selectively coat materials through a variety of accretion phenomena. The jet itself also has the potential to serve as analysis/metrology tool. The potential to unify a broad range of site-specific manufacturing methods under one platform presents a unique opportunity to enable bespoke programmable surface geometries, finishes and compositions, guided by design and independent of material precondition. This review seeks to enrich the literature by drawing together these interdisciplinary research avenues into a single extensive but critical literature survey, incorporating the process fundamentals and theory, recent developments, and applications of jet processing methods, including hybrid jet processes. Finally, this review attempts to provide new insight and propose the direction of future research with the view to enhancing the areas in which electrochemical jet processes can add value on the factory floor and become widely applied industrial practice. Graphical abstract: Image 1 Highlights: The state-of-the-art in electrochemical jet processes is discussed, with emphasis on fundamentals and applications. Mechanisms of removal, accretion, and surface modification with electrolyte jets are explored. Investigations of effects of common parameters on typical process outputs are critically reviewed. Prospective research areas for electrochemical jet processes are discussed in the context of topical manufacturing themes.